Effect of sports training programme on juvenile sports dancers motivation - B.A. Uspuriene; S.A. Sniras (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Lately, the researchers have paid more and more attention to the issues of sport motivation of exercising schoolchildren, but there are few scientific studies drawing the attention of researchers to  sports training programme effect on juvenile sports dancers motivation. Purpose: to verify the effectiveness of sports training programme on the expression of juvenile (9-11 years old) sports dancers sport motivation. Material: A scheme of the research of three groups was applied by using the initial and final measurements. The initial research was performed before the experiment and the final research was performed after the experiment, during the sports practice by using the sport motivation scale (SMS). 54 junior (9-11) dancers participated in the pedagogic experiment and they were divided into three groups: EG-1 - first experimental group, EG-2 - second experimental group, CG - control group. Each group consisted of 9 girls and 9 boys. The groups that participated in the experiment performed sports training programmes with the different diversity of methods and means. Kholmogorov - Smirnov test and Wilcoxon Z criterion were used for the descriptive index analysis in order to compare two independent samples. Results: The results of the research showed that the expression of the sport motivation-indicating subscales increased statistically significantly in groups EG-1 and EG-2 of juvenile (9-11) dancers in the 12-week period of the pedagogic experiment: "to find out", "to strive for perfection", "to experience". The intensity of the subscale of "amotivation" did not increase statistically reliably in the period of the pedagogic experiment (p>0,05). Moreover, it was determined that the internal motivation-indicating subscale "to strive for perfection" was the most expressed in the junior dancers. Conclusions: the diversity of sports training methods and means applied during the pedagogic experiment had a positive influence on the expression of sport motivation in the juvenile (9-11) dancers. After the sports training programmes, there were statistically significant changes in the both experimental groups in relation with the effect of the sports training programme according to the expression of the internal motivation-indicating subscales: "to find out", "to strive for perfection" "to experience" and of the external motivation-indicating subscales: "direct external regulation" and "to identify, synchronize".